Peace education - Harris, Ian M. 1943-; Morrison, Mary Lee 1947- (McFarland & Company, Inc., Publishers, 2013)
"Now in its third edition, Peace Education provides a comprehensive approach to educating for a just and sustainable future. It begins with religious and historical trends that have molded our understanding of "peace" and then presents a variety of ways to practice Peace Education in schools and communities and explains how it can empower students"--Provided by publisher